Harakter vydelitel'nogo affiksa -i i vopros of kategorii vydelitel'nosti v chuvashskom jazyke - Luutonen Jorma (Russian Federation, 2022)
[Title]  The character of the distinctive affix ‑i and the question of the category of distinction in the Chuvash language
In the article, the "distinctive suffixes" of the Chuvash language -i, -χi, and -sker, as well as the third person possessive suffix -i /-ĕ expressing definiteness, are investigated on the basis of grammatical literature. The author agrees with some Chuvash scholars that regard the "category of distinction" as problematic but considers "distinctive suffix" to be an appropriate name for the suffix ‑i, which combines the characteristics of  the Turkic distinctive suffix *-ki and the definite possessive suffix.  The author also discusses the absence of ‘marking definiteness’ among the functions of the possessive suffixes in Chuvash grammatical tradition.